Effectiveness of Implementing Modified Mindfulness Based Stress Reduction (MBSR) on Stress and Fatigue in Hemodialysis Patients - Aprianto Guntur Irawan; Dhea Natashia; Dewi Gayatri; Wati Jumaiyah; Winda Yuniarsih (Jurnal Ners, 2025)
Stress and fatigue are common complaints among hemodialysis patients, significantly affecting their quality of life during long-term therapy. This study aimed to evaluate the effectiveness of a modified Mindfulness-Based Stress Reduction (MBSR) intervention on stress and fatigue in patients undergoing hemodialysis. The study adopted a quasi-experimental pretest-posttest control group design and employed simple random sampling. A total of 32 respondents participated, with 16 in each group. Stress was measured using the Perceived Stress Scale (PSS-10) and fatigue using the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F 40). The modified MBSR intervention was conducted for 30 minutes per session. Data were analyzed using paired t-tests and independent t-tests. The results showed significant differences in stress (MD = -13.12, t = -4.748, p < 0.001) and fatigue levels (MD = 7.34, t = -3.865, p = 0.001) between the intervention and control groups. These findings indicate that the modified MBSR therapy was effective in reducing stress and fatigue, with a p-value < 0.05 indicating statistical significance. Therefore, this modified MBSR therapy is a promising non-pharmacological nursing intervention that can be integrated into nursing care for chronic kidney failure patients experiencing stress and fatigue during hemodialysis.